Peningkatan kreativitas menyusun gerak tari kreasi daerah melalui model pembelajaran contextual teaching learning di kelas IV sekolah dasar - Galuh Ayu Sekar Pramesthi; Siti Wahyuningsih; Hasan Mahfud (Universitas Sebelas Maret, 2021)
The aim of this research was to improve student’s creativity on composing dance movement creation of fifth A grade students of Kleco II Surakarta Elementary School in the academic year 2018/2019 with applied Contextual Teaching Learning (CTL) learning model by regional song media. This Classroom Action Research (CAR) was conducted of two cycles. Each cycle was held in two confluences which consistof four activities, they were planning, action, observation, and reflection. The subject of this reasearch was 30 students in class IV A of Kleco II Surakarta Elementary School in the academic year 2018/2019. The data collection consists of interviews, observations, performance tests, and activity documentations. This research used the content validity test with the qualitative data analysis developed by Miles and Huberman. The results of this research show that the student’s creativity on composing dance movement creation after action through Contextual Teaching Learning (CTL) learning model by regional song media. This was proved from the increasing average value of creativity in pre-action as 69,67 to 71,17 in the first cycle and 76,00 in the second cycle. Pre-action data showed classical completeness reached 40%, increased to 46,6% in the first cycle and the second cycle reached 96,55%. The conclusions of this research was the application of Contextual Teaching Learning (CTL) learning model could improved the student’s creativity on composing dance movement creation of fifth A grade students of Kleco II Surakarta Elementary School in the academic year 2018/2019.